The Accuracy of Pre-Operative Ultrasonography in Localizing Parathyroid Adenoma for Minimally Invasive Parathyroidectomy (MIP) - Yar Mohammad, Adnan; Anwar, Khurshid; Khan, Saeed; Rehman, Fazal (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To determine the sensitivity of pre-op ultrasonography in localizing parathyroid adenoma for minimally invasive parathyroidectomy (MIP) technique. METHODOLOGY The study was conducted at the department of ENT and Head & Neck Surgery, MTI Hayatabad Medical Complex Peshawar. It included a retrospective analysis of records of patients who underwent MIP from Jan 1, 2019, to July 31, 2022. All patients had pre-operative meta-iodobenzylguanidine (MIBG) scans, and serum PTH, Serum calcium levels were determined. A pre-op ultrasound scan was acquired to mark the site of the parathyroid adenoma. MIP was carried out using a 3.5 to 4 cm transverse skin incision over the marked site to expose the thyroid gland. If the marked parathyroid gland was identified without using any other aids, the result was labelled as "True positive". The sensitivity of pre-op ultrasonography was calculated using SPSS v 26.0. RESULTS A total of 53 cases were included in the study. The male: female ratio was 1:1.8. The ages of patients ranged from 23-70 years with a mean age of 48.49 years with a standard deviation of +_ 10.818. Pre-op ultrasonography accurately localizes the site of parathyroid adenoma in 49 patients. Statistical analysis showed this to be a significant finding. CONCLUSION Pre-op ultrasonography is significantly helpful in localizing the parathyroid adenoma. Therefore its routine use is recommended to help localize the adenoma in minimally invasive parathyroidectomy.